2013
DOI: 10.1039/c3ta10641a
|View full text |Cite
|
Sign up to set email alerts
|

High capacity micro-mesoporous carbon–sulfur nanocomposite cathodes with enhanced cycling stability prepared by a solvent-free procedure

Abstract: The use of elemental sulfur as a cathode active material is challenging. Besides the complex electrochemical conversion mechanism there are negative side effects added to the system by application of solvent-based cathode preparation, such as chemical incompatibility caused by solvent contamination, sulfur evaporation and morphology change during drying as well as limited active material loading. Therefore we present a solvent-free, highly versatile pressing/thermal treatment method for the fast and reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 30 publications
2
114
0
Order By: Relevance
“…Recently, Wang and co-workers reported a mesoporous carbon-sulfur composite microspheres by combining emulsion polymerization and the evaporation-induced self-assembly process with a sulfur content of 60 wt% and a high sulfur loading of 5.0 mg cm -2 afforded a reversible capacity of 740 mAh g -1 after 50 cycles [48]. Kaskel and co-workers presented a highly flexible freestanding carbon-sulfur composite cathode foils containing of 53 wt% sulfur, 27 wt% porous carbon host, 10 wt% CNT conducting agent, and 10 wt% poly(tetrafluoroethylene) binder afforded a maximal discharge capacity of 1045 mAh g -1 as well as a high reversible capacity of 742 mAh g -1 after 160 cycles at a high sulfur loading of 3.0-3.2 mg cm -2 [49]. In this contribution, although the sulfur ratio was very high, the sulfur can be utilized in high efficiency and good stability.…”
Section: Electrochemical Performance Of Flexible Paper Cathodementioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Wang and co-workers reported a mesoporous carbon-sulfur composite microspheres by combining emulsion polymerization and the evaporation-induced self-assembly process with a sulfur content of 60 wt% and a high sulfur loading of 5.0 mg cm -2 afforded a reversible capacity of 740 mAh g -1 after 50 cycles [48]. Kaskel and co-workers presented a highly flexible freestanding carbon-sulfur composite cathode foils containing of 53 wt% sulfur, 27 wt% porous carbon host, 10 wt% CNT conducting agent, and 10 wt% poly(tetrafluoroethylene) binder afforded a maximal discharge capacity of 1045 mAh g -1 as well as a high reversible capacity of 742 mAh g -1 after 160 cycles at a high sulfur loading of 3.0-3.2 mg cm -2 [49]. In this contribution, although the sulfur ratio was very high, the sulfur can be utilized in high efficiency and good stability.…”
Section: Electrochemical Performance Of Flexible Paper Cathodementioning
confidence: 98%
“…The excellent lithium ion storage performance of the GMS electrode reported herein was attributed to the following aspects: 1) 3D interconnected porous graphene networks for high sulfur capacity, sustaining huge volume change and retaining intimate electrical contact, 2) space confining property of graphene nanocage building blocks to retard severe dissolution of polysulfides, 3) both mechanically and 21 chemically robust CNT scaffolds to form binder-free interconnected electron channels instead of organic binder and metal current collector, improving long-term lifespan with high stability, and 4) the short-range graphene walls of the GMSs and long-range CNT scaffolds served as electron pathways [48][49][50], the 3D interconnected pores in the GMS particle and among CNTs used as ion channels for rapid transportation in the GMS/CNT composite cathode, consequently, this rendered a 46.7 % retention when the current density increased from 0.14 to 1.35 A cm -2 . If other porous long rang current collector/binder can be employed, such as graphene foam [51] or 3D porous carbon fiber scaffolds [52,53] were employed, flexible electrode with high areal capacity was highly expected, even the areal loading amount was as high as commercial loading amount of 4-15 mg cm -2 .…”
Section: Electrochemical Performance Of Flexible Paper Cathodementioning
confidence: 99%
“…(note that coin cells do not cause any problems even when freestanding electrodes are used since the largest area of an electrode can contact with a "current-collecting" casings of coin cells); (2) mass-loading tends to be extremely low (2 mg/cm 2 or less), resulting in a low capacity per unit area. Sulfur/micro-mesoporous carbon (MC)/Teflon (PTFE)/CNT free-standing sheets (80 µm thick) offer 2.3 mAh/cm 2 , and the preparation process of the sheets (roll-press) is suitable for mass production (Thieme et al, 2013); however, the free-standing cathode sheet was laminated onto a carbon-coated expanded aluminum current collector in order to reduce contact resistance. Lu et al (2014) reported that sulfur/graphene oxide (GO) sponges can offer a 12 mg/cm 2 of mass-loading and a 4.5 mAh/cm 2 or higher capacity at 0.1 C up to 300 cycles; however, the preparation method of the sponge (hydrothermal reduction of GO hydrogel in an autoclave) is problematic for the mass production of electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, several challenges need to be overcome, such as the extensive expansion and shrinking of the active material [15] as well as the repeated dissolution and deposition of insulating sulfur compounds [16,17]. Therefore, initiated by Nazar et al 2009 [18], a huge number of porous carbons with varying pore structures have been explored as conductive host for the active sulfur species [7,[19][20][21][22][23]. Particularly of importance for high capacity lithium-sulfur batteries is according to investigations of Li et al [24] as well as Liang et al [25] a multimodal pore system with significant differences in pore size especially micro-and mesopores due to the synergistic advantage of both pore systems, which can trigger an improvement of performance under realistic application oriented conditions.…”
Section: Introductionmentioning
confidence: 99%